Analysis of mechanical properties and micro-mechanisms of concrete based on the method of using steel slag as aggregate replacement: Macro-mechanical tests and microscopic tests of four typical control groups - Xiaobing Chen; Hengyi Yang; Jinhu Tong; Wei Hu; Fengyi Kang; Miao Zhang; Laiyuan Mao; Ronglong Zhao (PLoS ONE, 2026)
There is still controversy over whether the mechanical properties of steel slag concrete are superior to those of ordinary crushed-stone concrete and which method of substituting steel slag for aggregates yields better mechanical performance. Four groups of specimens were designed in this study, namely ordinary crushed-stone concrete, coarse steel-slag natural-sand concrete, crushed-stone fine steel-slag concrete, and all-steel slag concrete. The compressive strength, flexural strength, splitting tensile strength and failure morphology of the four groups of specimens were tested. Meanwhile, microhardness, scanning electron microscopy, X-ray diffraction, and Fourier-transform infrared spectroscopy tests were conducted to analyze the differences in their mechanical properties from a microscopic perspective. The corresponding test results indicated that: (a) Under the test conditions of this study, the order of compressive strength, flexural strength, and splitting tensile strength of concrete is ordinary crushed-stone concrete < coarse steel-slag natural-sand concrete <crushed-stone fine steel-slag concrete < all-steel slag concrete. (b) Steel slag fine aggregates are superior to steel slag coarse aggregates in enhancing the mechanical properties of concrete. Crushing steel slag coarse aggregate into steel slag fine aggregate to replace ordinary fine aggregates is more effective in enhancing mechanical strength than directly using coarse steel slag to replace coarse aggregates. When steel slag simultaneously substitutes for both coarse and fine aggregates, the concrete strength is the highest. Despite limitations of this study, the above conclusions, if further validated by future studies, will provide valuable references for further research on steel slag concrete.